2022
DOI: 10.1097/ijg.0000000000002090
|View full text |Cite
|
Sign up to set email alerts
|

3-Year Outcomes of XEN Implant Compared With Trabeculectomy, With or Without Phacoemulsification for Open Angle Glaucoma

Abstract: Précis: Trabeculectomy (TRAB) surgery reduces the intraocular pressure (IOP) more than the XEN45 implant over 3 years. There is no difference in the number of antiglaucoma medications between the 2 procedures. The decision to perform either TRAB or XEN45 implantation must be evaluated on a case-by-case basis, taking into account the high rate of needling of the XEN45. Purpose: The aim of this study was to compare the differences between the efficacy and safety of the XEN45 implant and TRAB, either alone or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 48 publications
1
6
2
Order By: Relevance
“…From a clinical point of view, different studies have reported the mid-and long-term efficacy, in terms of IOP lowering and the amount of ocular-hypotensive medications reduction, and safety of XEN45 implant, either alone or in combination with phacoemulsification surgery, in OAG patients. 14,16,17,[25][26][27][28][29][32][33][34][35][36][37][38] In this respect, the results of the study do not differ significantly from the published evidence.…”
mentioning
confidence: 39%
See 1 more Smart Citation
“…From a clinical point of view, different studies have reported the mid-and long-term efficacy, in terms of IOP lowering and the amount of ocular-hypotensive medications reduction, and safety of XEN45 implant, either alone or in combination with phacoemulsification surgery, in OAG patients. 14,16,17,[25][26][27][28][29][32][33][34][35][36][37][38] In this respect, the results of the study do not differ significantly from the published evidence.…”
mentioning
confidence: 39%
“…26,39 According to the results of Chen et al, 40 both XEN-alone (mean difference: −7.8 mmHg; 95% CI: −8.21 to −7.38 mmHg, p<0.001) and XEN+Phacoemulsification (mean difference: −8.35 mmHg; 95% CI: −9.82 to −6.88 mmHg, p<0.001) significantly lowered the IOP. However, another systematic review and meta-analysis published by Wang et al 38 has shown different results. They found better results for XEN alone compared XEN+Phacoemulsification procedures in IOP lowering but not in the reduction of ocular hypotensive medications.…”
mentioning
confidence: 97%
“…There are limited data comparing XEN with trabeculectomy. The 2 procedures had similar IOP-lowering efficacy when the baseline IOP was in the low twenties; 133 whereas overall, trabeculectomy lowered IOP significantly more than the XEN 45 implant 134–136 …”
Section: Subconjunctival Spacementioning
confidence: 93%
“…The 2 procedures had similar IOP-lowering efficacy when the baseline IOP was in the low twenties; 133 whereas overall, trabeculectomy lowered IOP significantly more than the XEN 45 implant. [134][135][136] Comparing the XEN 45 and XEN 63, Fernandez-García et al 137 found no difference in the amount of IOP-lowering over 36 months. However, Evers et al 138 found a slightly lower IOP after XEN 63 (IOP reduction of 44.6% vs 40.1%).…”
Section: Outcome and Safetymentioning
confidence: 99%
“…Different studies have been published demonstrating the shortterm benefits and safety of XEN Gel Stent application in patients with open angle glaucoma [7][8][9]. However, results from prospective randomised controlled trials comparing trabeculectomy and XEN Gel Stent implantation are missing [10], and there are only a few published retrospective studies with follow-up data longer than one year [11][12][13]. Therefore, in our study, we aimed to compare in detail the long-term clinical outcome and safety of XEN Gel Stent implantation vs. trabeculectomy for primary open angle glaucoma and pseudoexfoliation glaucoma.…”
Section: Introductionmentioning
confidence: 99%